Sustainable development in Portuguese higher education institutions from the faculty perspective - Leal, Susana (2023)
Higher education institutions play a fundamental role and have great responsibility in promoting sustainability and achieving sustainable development goals. It is therefore essential to study the teacher's perceptions of incorporating sustainability since they are responsible for promoting competences and preparing citizens to respond with solutions to future challenges. The aim of this research is to analyse the perceptions of sustainability held by teachers at Portuguese public higher education institutions. A descriptive and exploratory study was conducted by administering an online questionnaire. The sample is made up of 444 teachers from different Portuguese public higher education institutions (54.1% women and 45.9% men). The results show that while most teachers believe higher education institutions promote the integration of sustainability in their activities, only 16% consider that sustainable development is holistically integrated in the institutions' different activities. About 30% of the teachers report that they largely or extensively integrate sustainable development in their curricular units, but only 20% of them state that higher education institutions provide regular or systematic training in SD. Teachers prefer to increase students' sustainable development education through conferences, seminars, or research projects. Almost 90% of teachers are concerned about climate change or the environment, but only 40% or less engage in sustainable development-related activities. Four clusters are also identified, representing teachers' different perceptions of the higher education institutions' promotion of sustainability, teachers' participation in sustainable development issues and concerns about climate change. Although teachers feel that sustainability is starting to be integrated in higher education institutions, this is not done holistically; moreover, differences are found between teachers in polytechnics and universities and between different scientific areas.